A Versatile Method for the Protection of Carbonyl Compounds by Camphor Sulfonic Acid - Yadav, Ram N.; Banik, Bimal Krishna (Current Organocatalysis, 2018)
Background: Carbonyl groups are important functional groups and they play a key role in organic chemistry. This group needs to be protected in multistep synthesis against various reagents for a counter-reaction. The effort towards developing an efficient methodology for the protection of carbonyl functional group is always a demanding reaction. The protection of carbonyl compounds for inhibiting their chemical reactivity is an important operation in chemistry. In this paper, camphor sulfonic acid-catalysed protection of various carbonyl compounds is developed. This method is simple, environmentally friendly and yields products in high yields. Method: Commercially available camphor sulfonic acid is used as organo-catalyst for the protection of carbonyl functionality. This catalyst is also employed for the protection of carbonyl functionality as thioacetal/mixed ketal in excellent yield. The newly synthesize compounds are characterized using 1HNMR, 13C NMR and IR spectroscopy. Result: A diverse carbonyl functional group is protected in excellent yield under mild reaction conditions. Conclusion: We have developed an efficient organocatalysed protection method of carbonyl functionality applicable to wide range of substrates.
Keywords: thioketalization